Developing a model of proper governance for removing interaction barriers between universities of medical sciences andindustries - shiva madahian; alireza manzari tavakoli; sanjar salajegheh; seyed morteza seyed ahmadi (Shiraz University of Medical Sciences, 2017)
Background and goal: The interaction between university and industry, due to its highly constructive and positive effects on technical, economic and social changes, was traditionally at the center of policy makers' and planners' attention. The aim of the present study was to explain barriers and challenges existing in the interaction between medical sciences universities and industry. Method: This present descriptive-correlational study used measuring method fto investigate the interaction among Medical Sciences University (School of Public Health). 1468 individuals participated in this study. Using Morgan scale, 321 people were selected as the sample. Two questionnaires were prepared by the researcher. The proper governance questionnaire contains political, economic, social, legal and cultural dimensions composed of 69 questions. The barriers between university and industry questionnaire covering 3 dimensions of individual interaction barriers, organizational interaction barriers and environmental interaction barriers is composed of 40 questions. Data analysis was done using SPSS, version 21. Results: Based on factor analysis of the data, the main dimension of proper governance respectively was cultural factors and among various factors of barriers between university and industry, environmental interaction dimension was considered as the most important one. Moreover, the results showed that there was a direct and meaningful relationship between dimensions of proper governance and interaction between university and industry variable. Conclusion: Based on the results of the present study, considering culture and cultural differences can help improve the interaction between university and industry.